(untitled) (Research, Society and Development, 2021)
Productive integration stands out as an important strategy in the allocation of resources for food production in the world, combined with sustainable aspects that result in increased productivity. The Integrated Agricultural Production System (SIPA) is composed of different productive models such as Integration of Livestock and Forestry - ILPF, Integration of Livestock and Forestry - ILP, Integration of Livestock and Forestry - IPF, Integration of Forest and Livestock - ILF, which synergistically provide lower production costs as benefits, higher soil quality and biodiversity, reduction in water consumption, reduction in the Emission of Greenhouse Gases (GHG), in addition to the optimization of the area, considered the main economic factor of production in agricultural activities. The integration especially contemplates the mutual benefits between the components and the specifics of each rural enterprise, and can be adopted by small, medium or large producers. The objective was to analyze the activities of government institutions in the State of Goiás, in line with the theme of integrated production systems. Methodologically, the study has a qualitative nature and as for the objectives, it is classified as exploratory and descriptive, through a survey of the actions of institutions linked to the agribusiness sector. Finally, it was concluded that the participation of government institutions is linked to institutional partnerships, projects and public-private partnerships together with educational, research and extension institutions, which through the Technological Reference Units - URTs, strengthen the propagation of models of integrated production.